Influence of treatment with quercetin on lipid parameters and oxidative stress of pregnant diabetic rats - Pereira Braga, Camila [UNESP]; Momentti, Ana Carolina [UNESP]; Barbosa Peixoto, Fernando [UNESP]; de Fátima Ferreira Baptista, Rafaela [UNESP]; dos Santos, Felipe André [UNESP]; Fava, Fábio Henrique [UNESP]; Fernandes, Ana Angélica Henrique [UNESP] (Canadian Science Publishing, 2013)
Among the numerous coadjuvant therapies that could influence the incidence and progression of diabetic complications, antioxidants and flavonoids are currently being tested in clinical trials. We investigated the effect of quercetin on biochemical parameters in streptozotocin-induced (60 mg/kg body mass, by intraperitoneal injection) diabetic rats. A total of 32 female Wistar rats were distributed among 4 groups as follows: control (G1); control treated with quercetin (G2); diabetic (G3); and diabetic treated with quercetin (G4). Quercetin administered to pregnant diabetic rats controlled dyslipidemia and improved lipid profiles in diabetes mellitus, regulated oxidative stress by reducing the generation of lipid hydroperoxides, and increased the activity of the antioxidant enzyme glutathione peroxidase.
Keywords: Diabetes mellitus; Lipid profile; Oxidative stress; Pregnancy; Quercetin; antidiabetic agent; glutathione peroxidase; lipid hydroperoxide; quercetin; streptozocin; animal experiment; antidiabetic activity; biochemistry; controlled study; drug effect; dyslipidemia; enzyme activity; female; food intake; nonhuman; oxidative stress; pregnancy diabetes mellitus; priority journal; rat; Animals; Antioxidants; Blood Glucose; Diabetes Mellitus, Experimental; Diabetes Mellitus, Type 1; Female; Glutathione Peroxidase; Lipid Peroxides; Lipids; Male; Oxidative Stress; Pregnancy in Diabetics; Rats; Rats, Wistar; Treatment Outcome